Congenital Heart Defects in IVF/ICSI Pregnancy: Systematic Review and Meta-analysis. Issue 6 (June 2018) - Giorgione, V.; Parazzini, F.; Fesslova, V.; Cipriani, S.; Candiani, M.; Inversetti, A.; Sigismondi, C.; Tiberio, F.; Cavoretto, P.
Abstract : (Abstracted from Ultrasound Obstet Gynecol 2018;51:33–42) Despite congenital heart disease (CHD) being the most common type of congenital defect, in the majority of cases, the etiology remains unclear. Previous studies analyzing the risk of CHD after in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) show a slightly elevated risk when compared with spontaneously conceived infants.